PENGARUH PENGETAHUAN LINGKUNGAN TERHADAP NIAT MEMBELI PRODUK HIJAU PADA MEREK “ATTACK” DENGAN KEPEDULIAN LINGKUNGAN SEBAGAI VARIABEL MEDIASI - Ginting, Ria Karina; Ekawati, Ni Wayan (E-Jurnal Manajemen, 2016)
The purpose of this study is to investigate the role of environmental concern in mediating the effects of environmental knowledge on the intention to buy green products on the brand of “Attack” in Denpasar. The sample of this study is 100 people, with a non-probability sampling method especially purposive sampling. Data collected through questionnaires research where data were then analyzed using path analysis. The results showed that the knowledge of the environment has a positive and significant impact on the intention to buy green products and environmental concern, as well as environmental concern has a positive and significant impact on the intention to buy green products
Keywords: : environmental knowledge, environmental concern, intention to buy green products